Komunikasi visual arsitektur lanskap: studi kasus animasi desain ruang terbuka hijau Kampus Sudirman Universitas Udayana - Naniek Kohdrata; Muhammad Yasin Arief Afandi; I Made Agus Dharmadiatmika (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
. An animated visual media contains design ideas and works as a media for a landscape architect to communicate with clients. This research aims to analyze and describe the audiences's perceptions in giving meanings based on their understanding on the animated Green Open Space Design of Sudirman Campus, Udayana University. This study applies a qualitative research method. Data were collected from in-depth interview process with some respondents. The respondents are considered as audiences whom are categorized into structural officials and project managers related from Udayana University. The respondents responses were analyzed using visual communication theory. The analysis covers the animated visual product and audiences reception towards the green open space design understanding based on the meaning of the message delivered by the animated visual, and finally clarifying the position of the meaning of the message. The result shows that visual power through the application of animation techniques, namely solid drawing, story board, sound effects and motion graphics can influence audience in creating their own meaning toward design ideas messages delivered. There are also differences in the audience's meaning position, namely the opposition position and the accepting position.